Why do men with prostate cancer discontinue active surveillance for definitive treatment? A mixed methods investigation. Issue 8 (18th May 2022) - McIntosh, Megan; Opozda, Melissa J.; O'Callaghan, Michael; Vincent, Andrew D.; Galvão, Daniel A.; Short, Camille E.
Abstract: Objectives: To explore the personal and/or medical reasons patients on active surveillance (AS) have, or consider having, further definitive treatment for their prostate cancer. Research suggests up to 50% of patients on AS will discontinue within 5 years, though reasons for discontinuation from the patient's perspective is under‐explored. Methods: Prostate cancer patients who were or had been on AS for at least 6 months were recruited. A questionnaire assessed reasons for receiving/considering definitive treatment and the extent to which reasons were personal or medical. Clinical information was extracted from a state‐level population registry. A subset of participants were interviewed to further explore questionnaire responses. Results: One‐hundred and‐three individuals completed the survey; 33 were also interviewed. Fifty‐four survey participants (52%) had discontinued AS for definitive treatment. Common reasons for discontinuation were evidence of disease progression, doctor recommendation, desire to act, and fear of progression. Many participants who considered or had treatment reported weighing medical and personal factors equally in their decision. Interview participants described strongly considering any amount of disease progression and personal factors such as fear of progression, family concerns, and adverse vicarious experiences when deciding whether to pursue treatment. Conclusion: Both medical and personal factors are considered when deciding whether to discontinue AS. Identifying predictors of discontinuation is essential for informing supportive care services to improve AS management.